The Benefits Management and Balanced Scorecard Strategy Map: How They Match - Gomes, J. (2014)
We are living in a period of enormous technological transformations and the organizations face new opportunities that the systems and information technology (IS/IT) implementations provide with the hope that these investments will help to increase productivity and business prosperity, meanwhile, several studies performed in public and private sectors have proven that the investments done in IS/IT have not brought the expected benefits. Some authors argue that the result of the studies that related investments in IS/IT and the increasing performance of the organizations in the last thirty years were far from true. In this paper the authors propose a link between the Benefits Dependency Network, from a Benefits Management approach, and a Strategy Map, from Balanced Scorecard, to improve the management of business benefits and to ensure that actions taken along the investment life-cycle lead to foreseen benefits realization. The goal of this integration is to build a framework that combines useful features of both methods. The authors sustain that they can be complementary. As a Strategy Map is committed with strategic alignment, communication and monitoring of strategy execution at all levels of an organization, a Benefits Dependency Network is aimed at explaining how benefits are going to be obtained through organizational change. Using the results of a case-study research, the authors explain how a Strategy Map can cross with the Benefits Dependency Network. The integrated contribution is meant to increase the investments effectiveness, giving to stakeholders the confidence on a clearer delivery path for their expected benefits.